Theoretically designed two-dimensional γ-C4O as an effective gas separation membrane for hydrogen purification. Issue 35 (30th July 2020) - Ning, Cai; Zhang, Yadong; Wang, Jing; Gao, Haiqi; Xiao, Chuanyun; Meng, Zhaoshun; Dong, Huilong
Abstract : γ-C4 O is theoretically designed based on the structure of γ-graphyne, and is highly promising for hydrogen purification from a H2 /CH4 mixture. Abstract : A high-performance gas separation membrane for hydrogen (H2 ) purification is still highly desirable for the sustainable development of our society. Based on the structure of γ-graphyne, we theoretically designed the two-dimensional nanomaterials γ-C4 X (X = O, S or Se) with intrinsic pores that may be suitable for gas separation. By first-principles calculations, we obtained the geometric structures of γ-C4 X, and confirmed that γ-C4 O and γ-C4 S are stable at room temperature. Due to the moderate size of the intrinsic pores, γ-C4 O exhibits a lower diffusion barrier and higher permeance for H2 than those of γ-C4 S. It is worth noting that at room temperature, the high selectivity (10 19 ) for separating H2 from a H2 /CH4 mixture by γ-C4 O shows great potential for H2 purification. Moreover, the classic molecular dynamics simulations at 300 K demonstrate that H2 can easily permeate through the intrinsic pores of γ-C4 O membranes with high permeability and selectivity, which supports our first-principles calculations.